Legal Protection of Perfume Industry in Saudi Arabia and the Challenge of Dupe Comparative Advertising: A Comparative Analytical Study - Bafarat, Njood (Journal of Legal Sciences, 2025)
The global perfume market has recently witnessed rapid growth in imitation fragrances, commonly referred to as “dupes.” These products replicate the scent profiles of luxury brands through reverse engineering and attract consumers due to their affordability. However, they raise complex legal questions, particularly in the field of intellectual property. This paper critically examines the extent to which Saudi legal frameworks protect the fragrance industry under intellectual property law, including patents, trade secrets, trademarks, and industrial designs. It also assesses the effectiveness of these mechanisms in safeguarding the core element of a perfume: its scent. The study further conducts a comparative analysis of how the United States, the European Union, and Saudi Arabia regulate dupe perfumes, particularly in relation to comparative advertising and consumer protection. It concludes that the Saudi legal framework is more closely aligned with the U.S. model than with the European approach. Under Saudi law, dupe perfumes are permitted as long as they are not counterfeit. Comparative advertising of such products is likewise permitted, provided that specific conditions are met.